Karakteristik Hubungan Muhammadiyah dan NU dalam Menggunakan Hisab dan Rukyat - Susiknan Azhari (Al-Jami'ah Research Centre, 2006)
This article studies the matter of ḥisāb and ru’ya, particularly conducted by the following two extremely well-known socio-religious organizations, NU and Muhammadiyah. The reason for this choice is that the two for most of Indonesian people is the symbol of difference, even, of dissension among its Muslims referring to the thought of lunar calendar in Indonesia. The choice and the usage of the two matters frequently take place to determine the beginning of Ramaḍān, Shawwāl, and Dhū’l-Ḥijja in spite of the others. Therefore, it is necessary to deal with how the relation between NU and Muhammadiyah is due to the matters. To find out the answer for the inquiry theoretical framework developed by Ian G. Barbour i.e.: Conflict, Independent, Dialogue and Integration will be exercised.